Competing Insertion and External Binding Motifs in Hydrated Neurotransmitters: Infrared Spectra of Protonated Phenylethylamine Monohydrate. Issue 2 (23rd December 2015) - Bouchet, Aude; Schütz, Markus; Dopfer, Otto
Abstract: Hydration has a drastic impact on the structure and function of flexible biomolecules, such as aromatic ethylamino neurotransmitters. The structure of monohydrated protonated phenylethylamine (H + PEA−H2 O) is investigated by infrared photodissociation (IRPD) spectroscopy of cold cluster ions by using rare‐gas (Rg=Ne and Ar) tagging and dispersion‐corrected density functional theory calculations at the B3LYP‐D3/aug‐cc‐pVTZ level. Monohydration of this prototypical neurotransmitter gives an insight into the first step of the formation of its solvation shell, especially regarding the competition between intra‐ and intermolecular interactions. The spectra of Rg‐tagged H + PEA−H2 O reveal the presence of a stable insertion structure in which the water molecule is located between the positively charged ammonium group and the phenyl ring of H + PEA, acting both as a hydrogen bond acceptor (NH + ⋅⋅⋅O) and donor (OH⋅⋅⋅π). Two other nearly equivalent isomers, in which water is externally H bonded to one of the free NH groups, are also identified. The balance between insertion and external hydration strongly depends on temperature. Abstract : ApPEAling hydration : Dispersion‐corrected calculations and infrared photodissociation spectra of cold and tagged protonated phenylethylamine monohydrate reveal the formation of an insertion isomer in which water inserts between the ammonium and the phenyl groups.